2020
DOI: 10.1016/j.ijid.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of losses in the latent tuberculosis cascade of care in Brazil: A retrospective cohort study

Abstract: Background: The present study evaluated factors associated with losses in the latent tuberculosis infection (LTBI) cascade of care in contacts of tuberculosis (TB) patients, in a referral center from a highly endemic region in Brazil. Methods: Contacts of 1672 TB patients were retrospectively studied between 2009 and 2014. Data on TB screening by clinical investigation, radiographic examination and tuberculin skin test (TST) were extracted from medical records. Losses in the cascade of care and TB incidence wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In case of p δ = 0, the delta-gap (Δ) was calculated, which is defined as the distance between the intervals in δ units. The delta-gap value was directly related with the difference in distribution of values between the groups; the higher the delta value, the greater the effect size ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…In case of p δ = 0, the delta-gap (Δ) was calculated, which is defined as the distance between the intervals in δ units. The delta-gap value was directly related with the difference in distribution of values between the groups; the higher the delta value, the greater the effect size ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…A similar result was found in a previous study by our group in a different cohort of 1,264 TB contacts and using TST instead of IGRA. The study found a LTBI prevalence of 41.9% and the incidence of active TB of 2/100,000 inhabitants [19]. LTBI was significantly more common in women, black/ pardo , older individuals, and active and secondhand smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The parent study also included participants who were asymptomatic contacts of pulmonary TB index cases. All TB contacts were actively screened for TB through clinical, radiologic, and microbiologic investigation (32). At the time of study enrollment, individuals not living with HIV who tested positive for QuantiFERON TB Gold-in-Tube (QFT) enzymelinked immunosorbent assay (Qiagen) and also exhibited a positive tuberculin skin test (TST) result (> 5 mm) were considered to have latent TB infection (LTBI), and individuals who were QFT-negative and had negative TST result (< 5 mm) were considered uninfected controls (30).…”
Section: The Brazilian Case-control Studymentioning
confidence: 99%